Psychology indicates overtraining in swimming - Lowensteyn, I.; Signorile, J. F.; Kwiatkowski, K.; Caruso, J.; Ferris, D.; Salhanick, D.; Perry, A.; Mancino, C. (Medicine & Science in Sports & Exercise, 1994)
Ten collegiate swimmers were studied over six months. Measurements were taken: (a) the first week of training, (b) mid-season, (c) during peak training, (d) at the beginning of taper, and (e) following the taper. Good markers of overtraining were considered to be those which showed a dose-response relationship between the variable and training yardage in the swimmers with no change in controls. A repeated measures factorial ANOVA was used to analyze the data. Results: The only variables to change significantly were: (a) the rating of daily functioning, (b) the rating of general state of well being, and (c) illness. Non-significant variables were percent body fat, orthostatic heart rate, maximal oxygen consumption, hemoglobin concentration, peak lactate, Profile of Mood States (POMS), and rating of sleep quality. A decrease in performance and a significant increase in the POMS were used as criteria to indicate excessive (acute) training fatigue or staleness (symptoms had to persist after two weeks of decreased training or rest). No swimmer exhibited staleness but three did exhibit acute fatigue. No variables showed consistent changes for all three swimmers. A number of markers tracked well with increases and decreases in yardage for the group, however, when applied to the three individuals no markers proved reliable. Implication. Perceptions of fatigue, well being, daily functioning, and illness were better than standard physiological measures for locating responses to training across a group of trained swimmers.